1993
DOI: 10.1029/93pa00320
|View full text |Cite
|
Sign up to set email alerts
|

Two Major Cenozoic Episodes of Phosphogenesis Recorded in Equatorial Pacific Seamount Deposits

Abstract: Sea_mount phosphorites have been recognized since the 1950s, but this is the first study to provide an in depth exploration of the origin and history of these widespread deposits. Representative samples from equatorial Pacific Cretaceous s•mounts were analyzed for chemical, mineralogical, and stable isotope compositions. The phosphorites occur in a wide variety of forms, but most commonly carbonate fluorapatite (CFA) replaced middle Eocene and older carbonate sediment in a deep water environment (>1000 m). Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
108
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 107 publications
10
108
0
2
Order By: Relevance
“…It may also be mentioned that evidence for open-system evolution of 87 Sr/ 86 Sr isotopic ratios in phosphorites resulting in resetted and unusually young Sr-stratigraphic ages has been reported by e.g., McArthur et al (1990), Compton et al (1990), Hein et al (1993), and Stille et al (1994). Modeling the behavior of Sr during diagenesis of carbonate rocks, DePaolo (1987, 1988) found that solution-reprecipitation rates decrease significantly with the age and depth of burial of the sediment and that increasing diagenesis resulted in a shift of the 87 Sr/ 86 Sr towards older stratigraphic ages.…”
Section: The Sources Of Ree Nd-and Sr-isotopesmentioning
confidence: 99%
“…It may also be mentioned that evidence for open-system evolution of 87 Sr/ 86 Sr isotopic ratios in phosphorites resulting in resetted and unusually young Sr-stratigraphic ages has been reported by e.g., McArthur et al (1990), Compton et al (1990), Hein et al (1993), and Stille et al (1994). Modeling the behavior of Sr during diagenesis of carbonate rocks, DePaolo (1987, 1988) found that solution-reprecipitation rates decrease significantly with the age and depth of burial of the sediment and that increasing diagenesis resulted in a shift of the 87 Sr/ 86 Sr towards older stratigraphic ages.…”
Section: The Sources Of Ree Nd-and Sr-isotopesmentioning
confidence: 99%
“…The late Cretaceous to early Paleogene event may correspond to the 71 m.y. "minor" event of Hein et al (1993). A third event that occurred during the early middle Eocene seems to correspond temporally with the deposition of Horizon A c biosiliceous sediments.…”
Section: Discussionmentioning
confidence: 99%
“…The latest Eocene to early Oligocene event corresponds precisely with a period of major phosphogenesis for the Pacific, as documented by Hein et al (1993). The late Cretaceous to early Paleogene event may correspond to the 71 m.y.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations